2013
DOI: 10.1111/ggi.12115
|View full text |Cite
|
Sign up to set email alerts
|

Functional decline over 2 years in older Spanish adults: Evidence from the Survey of Health, Ageing and Retirement in Europe

Abstract: Aim To evaluate the social, educational, health and behavioral predictors of physical functional decline in older Spanish adults. Methods Two-year longitudinal study based on 699 community-dwelling Spanish adults over 65 year-old participating in the Survey of Health, Ageing and Retirement of Europe (SHARE). Several predictors of a combined measure of functional disability were examined using logistic regressions. Results A decline in function was experienced by 166 individuals. Functional decline in men w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
7
0
3
Order By: Relevance
“…These characteristics are common in the group of people with disabilities in ADLs. [19][20][21][22] The comparisons between the results with previous research are complicated due to the considerable differences in the study populations and the heterogeneity of the definitions of homebound status. 6 Not surprisingly, increasing age was significantly associated with being a homebound person, consistent with previous research conducted with older people.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics are common in the group of people with disabilities in ADLs. [19][20][21][22] The comparisons between the results with previous research are complicated due to the considerable differences in the study populations and the heterogeneity of the definitions of homebound status. 6 Not surprisingly, increasing age was significantly associated with being a homebound person, consistent with previous research conducted with older people.…”
Section: Discussionmentioning
confidence: 99%
“…No risk factors were identified for ADL decline in our study. Longitudinal trials and systematic reviews also identified predictive or risk factors for functional decline related to increased age (ADL, IADL) (Balzi et al, 2010;den Ouden et al, 2013;Rodrigues et al, 2009), female gender (ADL) (den Ouden et al, 2013), depression symptoms (Lêng & Wang, 2013;Rodríguez López et al, 2013;Stuck et al, 1999), hypertension (ADL, IADL) (Balzi et al, 2010;Rodríguez López et al, 2013) and arthritis (ADL) (den Ouden et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking (Stuck et al, 1999), low education (Rodrigues, Facchini, Thume, & Maia, 2013), age (Balzi et al, 2010;den Ouden, Schuurmans, Mueller-Schotte et al, 2013;Rodrigues et al, 2009), female gender (den Ouden et al, 2013), depression symptoms (Lêng & Wang, 2013;Rodríguez López, Montero, Carmenate, & Avendano, 2013;Stuck et al, 1999), hypertension (Balzi et al, 2010;Rodríguez López et al, 2013) and arthritis (den Ouden et al, 2013) are factors that have also been linked to functional decline in follow-up studies. However, to the best of our knowledge, the present study is the first to investigate the relationship among anthropometric measurements, functional capacity scores, socioeconomic status, medical conditions and blood oxidative stress markers in community-dwelling elderly.…”
Section: Introductionmentioning
confidence: 99%
“…An important factor in the mortality rate in older adults, has been shown to be the maintaining of the person's functional capacity, and the loss of this is associated with higher morbidity …”
Section: Introductionmentioning
confidence: 99%